Formation mechanism and optical characterization of polymorphic silicon nanostructures by DC arc-discharge1. Issue 84 (16th September 2015) - Yu, Jieyi; Gao, Jian; Xue, Fanghong; Yu, Xiuhong; Yu, Hongtao; Dong, Xinglong; Huang, Hao; Ding, Ang; Quan, Xie; Cao, Guozhong
<x xml:space="preserve">Abstract</x> Polymorphic Si nanostructures (particle, sheet, ribbon) are generated through isotropic, anisotropic, and coalescence growth using a DC arc-discharge plasma method.